EXPANDING HUMAN RIGHTS AND CIVIL RIGHTS VIOLATIONS IN THE UNITED STATES: SEE SOMETHING, SAY SOMETHING POLICY - Raines, Julie B.; Pinna, John T. (European Scientific Journal, ESJ, 2015)
According to the Bureau of Justice Statistics, almost 300,000 hate crimes occurred in 2012 in the United States. An astonishing 90% of these crimes were violent. Even more shocking are the 60% of hate crimes that are not reported to law enforcement (Wilson, 2014). In response to these dismal reporting statistics, the Department of Homeland Security (“DHS”) has adopted a policy (the “Policy”) and Congress introduced the “See Something, Say Something Act” (the “Act”), an amendment to the Homeland Security Act of 2002. The Policy and the Actencourage ordinary citizens to suspect and report someone based on perceived demeanor and/or overall appearance without the usual requirement of articulable suspicion (Terry, 1968). Due to the discriminatory nature of both the Policy and the Act, the proposed measures would be subject to strict scrutiny if challenged in court. Challenges to the Act would most likely revolve around civil rights violations. More importantly, basic human rights as outlined in the articles of The Universal Declaration of Human Rights (“UDHR”) are at issue.In practice, encouraging U.S. citizens to report each other without articulable suspicion opens the door for bias, prejudice, and intolerance. Even without these limitations, the Act may not achieve its ultimate goal of increasing reporting as only four percent of the 40% of hate crimes reported actually result in an arrest (Wilson, 2014). Increasing reporting of hate crimes, at best, may improve arrest rates into double digits.